An analysis of non-traditional activities at German savings banks: Does the type of fee and commission income matter? - Matthias Köhler (Deutsche Bundesbank, 2018)
In this paper, we use a fully anonymized dataset provided by the German Savings Banks Association (DSGV) to analyse which savings banks have expanded into fee-producing activities more quickly. In addition, we investigate whether their profitability and stability is correlated with the share of their fee and commission income. Notably, we examine whether the effect on bank profitability differs depending on the type of fee and commission income. Our results support the view that savings banks with low net interest margins are under greater pressure to expand into fee-producing activities. They further suggest that savings banks with a higher share of fee and commission income, in particular from payment services and securities business, also have a higher profitability. The Z-score also correlates positively with the share of securities business income, possibly because it responds to different shocks than net interest income and, therefore, offers the largest diversification potential.
Keywords: G20; G21; G29; 330; savings banks; fee and commission income; profitability